Gender, age and physical activity representation in children’s colouring books - Martínez Bello, Vladimir; Hill, Joanne (Cuestiones de Género: de la igualdad y la diferencia, 2020)
Despite publishing houses recognizing the importance of ensuring equal representation of all people in curricular materials and scholars also noting their importance in teaching children gendered behaviours, it is still common to find stereotypically gendered non-coeducational curriculum materials in the international market. The aim of this study is to determine the representation of female and male characters in the illustrations of six colouring books published in the United Kingdom entitled “Books for Girls” and “Books for Boys”. A quantitative content analysis, and a supporting qualitative discourse analysis were carried out. This paper examines the effect of constructing gender difference in children’s colouring books. Gender bias in early childhood education poses the risk of perpetuating a manifestation of inequality.